2019
DOI: 10.1007/s11274-018-2587-4
|View full text |Cite
|
Sign up to set email alerts
|

Bio-conversion of methane into high profit margin compounds: an innovative, environmentally friendly and cost-effective platform for methane abatement

Abstract: Bio-conversion of methane into high profit margin compounds: An innovative, environmentally friendly and cost-effective platform for methane abatement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 61 publications
0
17
0
1
Order By: Relevance
“…The localized nature of many of these anthropogenic emissions, makes it possible to implement end-of-pipe abatement technologies. In this context, the use of methanotrophic organisms constitutes an efficient solution for methane abatement, and also offers the possibility of transforming a waste gas into marketable chemicals and commodities [ 5 ], thus contributing to the development of a circular economy. The cost of glucose, which is the most commonly used substrate in industrial biotechnology, can account for 30% of the total production costs, which makes methane a very attractive alternative [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The localized nature of many of these anthropogenic emissions, makes it possible to implement end-of-pipe abatement technologies. In this context, the use of methanotrophic organisms constitutes an efficient solution for methane abatement, and also offers the possibility of transforming a waste gas into marketable chemicals and commodities [ 5 ], thus contributing to the development of a circular economy. The cost of glucose, which is the most commonly used substrate in industrial biotechnology, can account for 30% of the total production costs, which makes methane a very attractive alternative [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methanol can be derived from the gasification of biomass to synthesis gas with subsequent reduction to methane, followed by oxidation to methanol. This can be achieved chemically or biologically via a variety of emerging technologies [2,3]. These processes would enable the use of biomass, municipal waste, or natural gas as feedstocks for bio-production via methanol, enabling independence from arable land and sugar production.…”
Section: Introductionmentioning
confidence: 99%
“…The most common feedstock used for production of PHAs are glucose and fructose, but those carbon sources have a high price, due the market price of PHAs is higher (4-20 € KgPHA -1 ) (Koller et al, 2017). PHAs are currently industrially produced by nearly thirty corporations (Cantera et al, 2019). An innovative feasible alternative to enhance the economic sustainability of the degradation and valorization of CH 4 combined to the concomitant replacement of common plastics is the coproduction of polyhydroxyalkanoates (PHAs) combined with the treatment of methane emissions (Cal et al, 2016;Pieja et al, 2017;Strong et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…An innovative feasible alternative to enhance the economic sustainability of the degradation and valorization of CH 4 combined to the concomitant replacement of common plastics is the coproduction of polyhydroxyalkanoates (PHAs) combined with the treatment of methane emissions (Cal et al, 2016;Pieja et al, 2017;Strong et al, 2016) . Indeed, several studies have demonstrated that methanotrophs are a potential source of bioplastics, achieving PHA contents ranging from 20 to 60 % (wt) using methane as feedstock (Cantera et al, 2019;Pieja et al, 2017). Methanotrophs are divided into two different groups according to the pathway for carbon assimilation a) type I (-proteobacteria) use the ribulose monophosphate (RuMP) pathway or b) type II (-proteobacteria) use of the serine pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation